Role of Protein Kinase A-Mediated Phosphorylation in CFTR Channel Activity Regulation - Della Sala, Angela; Prono, Giulia; Hirsch, Emilio; Ghigo, Alessandra (Frontiers in Physiology, 2021)
Cystic fibrosis transmembrane conductance regulator (CFTR) is an anion channel expressed on the apical membrane of epithelial cells, where it plays a pivotal role in chloride transport and overall tissue homeostasis. CFTR constitutes a unique member of the ATP Binding Cassette (ABC) transporter superfamily, due to its distinctive cytosolic regulatory (R) domain carrying multiple phosphorylation sites, that allow the tight regulation of channel activity and gating. Mutations in the CFTR gene cause cystic fibrosis, the most common lethal autosomal genetic disease in the Caucasian population. In recent years, major efforts have led to the development of CFTR modulators, small molecules targeting the underlying genetic defect of CF and ultimately rescuing the function of the mutant channel. Recent evidence has highlighted that this class of drugs could also impact on the phosphorylation of the R domain of the channel by protein kinase A (PKA), a key regulatory mechanism that is altered in various CFTR mutants. Therefore, the aim of this review is to summarize the current knowledge on the regulation of the CFTR by PKA-mediated phosphorylation, and to provide insights into the different factors that modulate this essential CFTR modification. Finally, the discussion will focus on the impact of CF mutations on PKA-mediated CFTR regulation, as well as on how small molecule CFTR regulators and PKA interact to rescue dysfunctional channels.